2015
DOI: 10.9738/intsurg-d-14-00138.1
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Monitoring During Heated Intraoperative Intraperitoneal Chemotherapy Using the FloTrac/Vigileo System

Abstract: Cytoreductive surgery with HIPEC has provided a chance for long-term survival in selected patients. However, perioperative management remains a challenge for the anesthesiology team. The aim of this study was to evaluate the changes in hemodynamic parameters during hyperthermic intraperitoneal chemotherapy (HIPEC) using the FloTrac/ Vigileo system. Forty-one consecutive patients undergoing cytoreductive surgery and HIPEC were enrolled. Heart rate (HR), esophageal temperature, and cardiac output (CO) steadily i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Changes in MAP in response to HIPEC are variable, with few studies showing stable MAP and others showing a significant decrease. [ 3 10 11 12 ] MAP variations are also governed by the use of vasopressors (norepinephrine), intravascular volume and changes in SVR. But in the present study, the use of vasoactive drug support, blood loss and administered fluids in both groups were comparable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in MAP in response to HIPEC are variable, with few studies showing stable MAP and others showing a significant decrease. [ 3 10 11 12 ] MAP variations are also governed by the use of vasopressors (norepinephrine), intravascular volume and changes in SVR. But in the present study, the use of vasoactive drug support, blood loss and administered fluids in both groups were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in HR has been reported in previous studies also attributed to the body's initial responses to hyperthermia, to maintain CO in the face of decreasing SVR, splanchnic heating or abdominal distention. [ 2 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 27 ] Functional hemodynamic monitoring in the form of CO, SVV and DELTA SV particularly when PCI is recommended >15 to guide the goal directed fluid therapy to maintain normovolemia and prevent acute renal failure. [ 28 ] Extravascular lung water (EVLW) is the amount of water that is present outside the pulmonary vasculature. It includes interstitial, intracellular, alveolar and lymphatic fluid and does not include pleural effusions.…”
Section: Intraoperative Concernsmentioning
confidence: 99%
“…[ 13 14 ] The non-invasive cardiac output monitoring and urine output appear to be an acceptable monitoring tool in such surgeries. [ 17 ] The fluid management was guided by non-invasive continuous cardiac output monitoring with FloTrac in patients with high tumour load and patient having persistent haemodynamic perturbations in the study being published. [ 10 ] Another randomised controlled trial which studied various outcomes related to CRS and HIPEC reported that the use of a goal-directed fluid therapy using the FloTrac/Vigileo was associated with improved patient-related outcome for major abdominal and systemic post-operative complications and reduced length of hospital stay.…”
Section: Fluid Managementmentioning
confidence: 99%